Pengaruh durasi pemberian air susu ibu terhadap intercanine distance dan intermolar distance pada anak usia 4 - 5 tahun di Taman Kanak-Kanak Handayani Denpasar - AA B Dasta Budawangsa; Louise Cinthia Hutomo; Luh Wayan Ayu Rahaswanti (School of Dentistry Faculty of Medicine Udayana University, 2019)
Introduction: Some studies have reported that breastfeeding duration can affect the growth and development of the children’s jaws. It happens because the oral motion of the baby during breastfeeding is actually a combination of sucking, chewing, swallowing and breathing which can stimulate the growth and development of the jaw arch including the arch width and the occlusion pattern of the child. The aim of this study is to determine the effect of breastfeeding duration towards the arch width by measuring the Intercanine Distance (ICD) and Intermolar Distance (IMD) in 4 to 5 years old children at Handayani Kindergarten Denpasar. Method: This is an analytical research with cross-sectional approach on 40 children whom selected with total sampling technique. The arch width data was collected by measuring ICD and IMD from each maxillary arch study model using a caliper, while breasfeeding duration data was collected by using questionnaire, and those data was analized with Fisher’s Exact Test. Result: the results of this study shows that there are significant differences in ICD in children with breastfeeding duration less than 6 months and children with breastfeeding duration is 6 months or more (p<0.05), and no significant difference in IMD (p>0.05). Conclusion: the conclusion of this study is the duration of breastfeeding affect the size of ICD, but it does not affect the size of IMD.